Staphylococcus aureus oleate hydratase produces ligands that activate host PPARα - Radka, Christopher D.; Frank, Matthew W.; Simmons, Tyler S.; Johnson, Cydney N.; Rosch, Jason W.; Rock, Charles O. (Frontiers in Cellular and Infection Microbiology, 2024)
Commensal gut bacteria use oleate hydratase to release a spectrum of hydroxylated fatty acids using host-derived unsaturated fatty acids. These compounds are thought to attenuate the immune response, but the underlying signaling mechanism(s) remain to be established. The pathogen Staphylococcus aureus also expresses an oleate hydratase and 10hydroxyoctadecanoic acid (h18:0) is the most abundant oleate hydratase metabolite found at Staphylococcal skin infection sites. Here, we show h18:0 stimulates the transcription of a set of lipid metabolism genes associated with the activation of peroxisome proliferator activated receptor (PPAR) in the RAW 264.7 macrophage cell line and mouse primary bone marrow-derived macrophages. Cell-based transcriptional reporter assays show h18:0 selectively activates PPAR Radiolabeling experiments with bone marrow-derived macrophages show [1-14 C]h18:0 is not incorporated into cellular lipids, but is degraded by -oxidation, and mass spectrometry detected shortened fragments of h18:0 released into the media. The catabolism of h18:0 was >10-fold lower in bone marrow-derived macrophages isolated from Ppara -/-knockout mice, and we recover 74-fold fewer S. aureus cells from the skin infection site of Ppara -/-knockout mice compared to wildtype mice. These data identify PPAR as a target for oleate hydratase-derived hydroxy fatty acids and support the existence of an oleate hydratase-PPAR signaling axis that functions to suppress the innate immune response to S. aureus. KEYWORDS oleate hydratase (OhyA), hydroxy fatty acid, macrophage, Staphylococcus aureus, peroxisome proliferator activated receptor alpha (PPAR), fatty acid oxidation, host-microbe interaction, signaling